Impact of Automation on Process Control Decision-Making - MILLER, Steven M. (Institutional Knowledge at Singapore Management University, 1987)
This paper investigates changes in the process control of a vehicle assembly plant which had been modernized from a principally manual procedure to one that uses programmable automation extensively. Process control is defined as the information flow and decision-making required to perform basic process operations. We investigate the effects of implementing a computer-integrated production system on the amount and types of process control decision-making and on the distribution of process control decision-making between humans and machines. After automation, the emphasis on decisions regarding product quality specifications increased and the emphasis on decisions related to flexibility in handling a variety of product options decreased. Decisions concerning product quality specifications, as well as timing and synchronization of tasks, were usually performed by automated equipment, while decisions relating to the flexibility of the process remained, to a large extent, under manual control. Whereas humans made nearly 75% of the decisions required to assemble and weld a vehicle body in the principally manual system, humans made fewer than 10% of similar decisions in the automated system.